Benign Fibroepithelial Polyp of Renal Pelvis in a Patient with Familial Adenomatous Polyposis: A Successful Percutaneous Nephroscopic Management Strategy. (6th December 2009) - Vasdev, Nikhil; Holmes, Philippa; Senior, Katie; Haslam, Philip; Hasan, Tahseen; Dorkin, Trevor
Abstract : We present a rare case of a benign fibroepithelial polyp of the renal pelvis in a patient with familial adenomatous polyposis. In our paper we describe a new minimally invasive technique developed in our unit using an amplatz goose neck snare via a percutaneous nephroscope sheath in the management of the benign fibroepithelial polyp of the renal pelvis and present a current review of management strategies in literature.